Sumillera, Rocío G./Surman, Jan/Kühn, Katharina (eds.) (2020): Translation in Knowledge, Knowledge in Translation. Amsterdam/Philadelphia: John Benjamins (Benjamins Translation Library 154). - Elsherif, Garda (chronotopos – A Journal of Translation History, 2022)
A book review of: Sumillera, Rocío G./Surman, Jan/Kühn, Katharina (eds.) (2020): Translation in Knowledge, Knowledge in Translation. Amsterdam/Philadelphia: John Benjamins (Benjamins Translation Library 154).